A protective effect of baicalin on cerebral ischemic rats is related to the improvement of serum progesterone level in serum. Issue 16 (6th November 2019) - Li, Haiyan; Wu, Lili; Wang, Donghui; Guo, Yangyang; Liu, Tonghua; Pan, Yanshu
Abstract : Baicalin, an ingredient drawn from Scutellaria amoena Georgi, plays a brain-protective role through anti-inflammatory, antioxidant, and other pathways. The aim of this study was to investigate the possible protective mechanism of baicalin on middle cerebral artery occlusion rats. Rats were divided into 4 groups: sham, middle cerebral artery occlusion, middle cerebral artery occlusion + baicalin, middle cerebral artery occlusion + baicalin treated + inhibitor (bromocriptine, which inhibit progesterone induction). After 7 days treatment, neurological deficits and infarct volume were determined, morphological change of penumbra was examined by (hematoxylin-eosin) staining. The expressions of neuronal nuclei (NeuN), glial fibrillary acidic protein (GFAP), and progesterone receptor were also assessed by immunofluorescent staining or immunohistochemistry, progesterone, and adrenocorticotropic hormone in serum were also determinated by ELISA. We found that baicalin could reduce the neurological deficits, infarct volume caused by middle cerebral artery occlusion, increase the expression of NeuN, GFAP, and progesterone receptor in ischemic penumbra and increase the expression of progesterone and adrenocorticotropic hormone level in serum. Those indicated that baicalin plays a protective role in cerebral ischemia rats by improvement of progesterone.